Role of Interventional Radiology in Endocrine Diseases- Review Article - Hossein GHANAATI; Kavous FIROUZNIA; Bagher LARIJANI; Amir Hossein JALALI (Tehran University of Medical Sciences, 2015)
Recently, a number of procedures for interventional radiology diagnosis and treatment have been developed by the radiologists. The 'Interventional Radiology' refers to the therapeutic procedures performed under imaging guidance. The emergence of this specialty has been made possible by a lot of advances in the technology, imaging systems, and radiologists experience. Interventional radiologists are physicians who are experienced in minimally invasive procedures and targeted treatments which have less risk, less pain and less recovery time in comparison with the surgery. Minimizing the patient discomfort, avoid of general anesthesia, lower incidence of morbidity and mortality, and decreases the length and cost of hospitalization are some advantages of interventional radiology procedures. Similar to all medical fields, interventional procedures have been introduced and developed for the diagnosis and treatment of endocrinology procedures. In this article we aim to review and report our experience about the role of interventional radiology in venous sampling for endocrine diseases (such as parathyroid venous sampling, inferior petrosal sinus sampling, adrenal venous sampling, and venous sampling for islet cell tumors). In addition, interventional treatments of neuroendocrine cancer metastases to the liver, percutaneous ethanol injection therapy for secondary hyperparathyroidism, treatment of hyperfunctioning thyroid nodules by percutaneous ethanol injection, radiofrequency ablation of the adrenal gland neoplasms, and also establishing a cGMP pancreatic islet processing facility have been discussed in this article.   Keywords: Interventional radiology, Endocrine diseases, Endovascular, Treatment